Untraceable - Cohen, Andy.; Koch, Howard W., 1945-; Lucchesi, Gary.; Pearl, Steven; Rosenberg, Tom.; Wright, Richard, 1960 August 1-; Fyvolent, Robert; Brinker, Mark R.; Burnett, Allison; Hoblit, Gregory; Lane, Diane; Burke, Billy; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2008)
Jennifer Marsh is an FBI secret service agent who gets caught up in a very personal and deadly cat-and-mouse game with a serial killer. The killer knows that people are drawn to the curious and the dark side of things. They will log onto an 'untraceable' website where the killer conducts violent and painful murders live on the internet. The more people who log on and enter the website, the quicker and more violently the victim dies.
English, French and Portuguese tracks: Dolby digital 5.1.
Spanish track.
Title from container.
Director of photography, Anastas Michos ; editor, David Rosenbloom ; music, Christopher Young ; costume designer, Elisabetta Beraldo ; production designer, Paul Eads.
Diane Lane, Billy Burke, Colin Hanks, Joseph Cross, Mary Beth Hurt, Peter Lewis, Tyrone Giordano, Perla Haney- Jardine, Tim De Zarn, Chris Cousins, Jesse Tyler Ferguson.
MPAA rating: R; for some prolonged sequences of strong gruesome violence, and language.
Keywords: United States. -- Federal Bureau of Investigation -- Drama; Computer crimes -- Investigation -- Drama; Serial murderers -- United States -- Drama; Internet -- Drama; Violent deaths -- United States -- Drama; Feature films; Thrillers (Motion pictures, television, etc.); Video recordings for the hearing impaired; Feature films; Suspense films